The Perilous Seat - Snedeker, Caroline Dale, 1871-1956 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Perilous Seat" by Caroline Dale Snedeker is a historical novel written in the early 20th century. The narrative is set in ancient Greece, focusing on the lives of the Nikander family, particularly the siblings Dryas and Theria, against a backdrop of cultural festivities and the Oracle of Delphi. The story delves into themes of creativity, jealousy, and familial bonds, showcasing the tensions between shared aspirations and personal recognition. At the start of the novel, we are introduced to the Pythian Festival, where young Dryas triumphantly wins a singing competition, bringing pride to his father, Nikander. However, the celebration is overshadowed by a conflict with his sister Theria, who claims the song that Dryas presented was originally hers. The opening chapters illustrate the dynamics of their family life, depicting Dryas's deep bond with his father and the ensuing tension when Theria struggles with feelings of jealousy and the desire for acknowledgment in her own artistic endeavors. As the story unfolds, the complexities of sibling relationships and the expectations placed upon them come to light amid their shared heritage in Delphi's vibrant culture. (This is an automatically generated summary.)
Release date is 2021-12-30
Mary Glenn Krause and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Historical fiction; Greece -- History -- Persian Wars, 500-449 B.C. -- Fiction; Delphi (Extinct city) -- Fiction